+0  
 
0
722
1
avatar

was ergibt -x^2-(+x^2)

 26.07.2015

Beste Antwort 

 #1
avatar+11086 
+5

Hallo anonymous!

 

was ergibt -x^2-(+x^2)

 

 - x² - (+ x²) = - x² - x² = - 2x²        Das Minus vor der Klammer

                                                     ändert + x² in - x² . Die Klammer entfällt .

 

 - x² - (+ x²) = - 2x²

 

:- )

 26.07.2015
 #1
avatar+11086 
+5
Beste Antwort

Hallo anonymous!

 

was ergibt -x^2-(+x^2)

 

 - x² - (+ x²) = - x² - x² = - 2x²        Das Minus vor der Klammer

                                                     ändert + x² in - x² . Die Klammer entfällt .

 

 - x² - (+ x²) = - 2x²

 

:- )

asinus 26.07.2015

67 Benutzer online

avatar
avatar
avatar
avatar
avatar